Business cycles and production networks - Maria Olsson (Uppsala University, Department of Economics, 2019)
Where do business cycles originate? The traditional view is that a business cycle is the result of shocks correlated across sectors. This view is complemented by a recently emerging literature showing that idiosyncratic shocks to large or highly interconnected sectors contribute to aggregate variation. This paper addresses the relative empirical importance of these two channels of business cycle variation. Results indicate that up to one-third of the business cycle is driven by idiosyncratic productivity variation together with network amplifications.
urn:nbn:se:uu:diva-388335
Keywords: 330; Production Networks; Micro to Macro; Aggregate Volatility; Sectoral Distortions